Implementasi Konsep Cheerful Pada Interior Health and Beauty Care for Baby and Kids di Surabaya - Natalia Sugiharto (Intra, 2013)
Development of the era that followed by the change in lifestyle of modern society makes the competition in the higher areas of the business. The impact of this competition seen in the field of spa business. Beauty and health care needs that initially was limited to only requirement is now considered a lifestyle of upper class society. Not only adults but children were also able to obtain health and beauty care with full facilities from head to toe. With the interior design of the Health and Beauty Care for Baby and Kids in Surabaya infants and children are pampered with full amenities ranging from hair care, massage and swimming, as well as manicure-pedicure. This design took the theme of "Cheerful" which means fun in the design which is expected to create a fun atmosphere that can support treatments for infants and children. Application of these themes led to the play of colors and shapes as well as comfortable and clean impression which became the focal point of this design. With the background of want to bring a complete treatments place for infants and children, the interior design of the Health and Beauty Care for Baby and Kids is expected to provide a supportive comfort and satisfaction of visitors, especially for babies and kids can feel happy and relaxed.